Reduced graphene oxide-gold nanoparticles-catalase-based dual signal amplification strategy in a spatial-resolved ratiometric electrochemiluminescence immunoassay. Issue 1 (19th November 2019) - Cao, Jun-Tao; Fu, Xiao-Long; Liu, Fu-Rao; Ren, Shu-Wei; Liu, Yan-Ming
Abstract : A novel spatial-resolved electrochemiluminescent (ECL) ratiometry for cardiac troponin I (cTnI) analysis was developed using resonance energy transfer (RET) and a coreactant consumption strategy for signal amplification. Abstract : A novel spatial-resolved electrochemiluminescent (ECL) ratiometry for cardiac troponin I (cTnI) analysis was developed using resonance energy transfer (RET) and a coreactant consumption strategy for signal amplification. Specifically, the spatial-resolved dual-disk glassy carbon electrodes were modified with CdS nanowires (CdS NWs) and luminol-gold nanoparticles (L-Au NPs) as potential-resolved ECL emitters, respectively. After stepwise immobilization of anti-cTnI and bovine serum albumin on the dual-disk electrodes, the CdS NWs-based electrode, with varied concentrations of cTnI, was used to provide a working signal, whereas the L-Au NPs-based electrode, with a fixed amount of cTnI, was employed to provide the reference signal. To efficiently amplify the working signal on the CdS NWs-based electrode, an anti-cTnI-reduced graphene oxide-gold nanoparticles-catalase probe (anti-cTnI-rGO-Au NPs-CAT) was loaded onto the electrode to form a sandwich immunocomplex. The RET from CdS NWs to Au NPs and the coreactant ( i.e. H2 O2 ) consumption by the CAT generate a significant ECL decrease on the CdS NWs-based electrode in the presence of cTnI. This novel and sensitive ratiometric detection mode for cTnI was achieved using the ratio values of the working signal of the CdS NWs-based electrode and the reference signal of the L-Au NPs-based electrode. The integration of RET and coreactant consumption strategy in the designed spatial-resolved ratiometric platform endows the immunosensor with a wide linear range of 5.0 × 10 −13 – 1.0 × 10 −7 g mL −1 and a low detection limit of 0.10 pg mL −1 for cTnI. Furthermore, the method exhibits high accuracy and sensitivity for cTnI determination in human serum samples.